EFL STUDENTS’ ENGAGEMENT IN READING COMPREHENSION USING COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TECHNIQUE - Devianne Dwi Utari Mahdahera; Iwan Ridwan (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2023)
The reading comprehension skills of EFL students have been a concern of scholars by researchers, but some researchers found that EFL students face some problems in understanding English texts due to lack of techniques while teaching. Therefore, this study investigates how students engage in reading comprehension using the Cooperative Integrated Reading Composition Technique. This study uses a case study as a qualitative research design, involving EFL tenth graders from an Islamic Senior High School in Karawang as participants. Researchers collect data through observation and interviews. The findings show that EFL students’ engagement in reading comprehension using the CIRC technique resulted in three engagements, namely behavioral engagement, emotional engagement, and cognitive engagement. Behavioral engagement which means students can contribute to class discussion and follow all instructions from the teacher, emotional engagement which means students can express their feelings during reading comprehension activities, and cognitive engagement which means students can try to complete tasks in different ways to achieve the same result. This research suggests that educators should expand or develop their teaching techniques to produce better learning activities.